2023
DOI: 10.3390/cells12151975
|View full text |Cite
|
Sign up to set email alerts
|

Slowing the Progression of Diabetic Kidney Disease

Olivia Blazek,
George L. Bakris

Abstract: Diabetes is the most frequent cause of kidney disease that progresses to end-stage renal disease worldwide, and diabetic kidney disease is significantly related to unfavorable cardiovascular outcomes. Since the 1990s, specific therapies have emerged and been approved to slow the progression of diabetic kidney disease, namely, renin–angiotensin–aldosterone system blockers (including angiotensin-converting enzyme inhibitors (ACEi) angiotensin receptor blockers (ARBs), the non-steroidal mineralocorticoid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Figure 3 shows the effects of SGLT2 inhibitors on inflammation and oxidative stress [82]. A study in mice with type 2 diabetes showed that SGLT2 inhibitors prevented renal tubular fibrosis [80]. Other studies show that these drugs can reduce abnormal cell remodeling by decreasing endothelial markers.…”
Section: Sodium-glucose Cotransporter Protein 2 (Sglt2) Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3 shows the effects of SGLT2 inhibitors on inflammation and oxidative stress [82]. A study in mice with type 2 diabetes showed that SGLT2 inhibitors prevented renal tubular fibrosis [80]. Other studies show that these drugs can reduce abnormal cell remodeling by decreasing endothelial markers.…”
Section: Sodium-glucose Cotransporter Protein 2 (Sglt2) Inhibitorsmentioning
confidence: 99%
“…An increase in the eNOS enzyme has been shown to inhibit pathological remodeling in diabetic kidney disease by restoring proper NO utilization and having a protective effect on both the renal endothelium and the cardiovascular system [83]. One of the main pro-fibrotic factors is growth factor 1 (TGF-1), which has potent profibrotic effects through the deposition of the extramesenchymal matrix, re- A study in mice with type 2 diabetes showed that SGLT2 inhibitors prevented renal tubular fibrosis [80]. Other studies show that these drugs can reduce abnormal cell remodeling by decreasing endothelial markers.…”
Section: Sodium-glucose Cotransporter Protein 2 (Sglt2) Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The driving factors for cardiovascular complications in diabetic patients including glucotoxicity, lipotoxicity, and hypertension ( Kenny and Abel, 2019 ). Meanwhile, diabetic kidney disease (DKD) is the most common cause of death among microvascular complications of diabetes and is closely associated with cardiovascular outcomes ( Blazek and Bakris, 2023 ). Currently, there has been a paradigm shift in the management of diabetes and its complications, with a focus on not only controlling blood glucose levels but also addressing the associated cardiovascular and renal risks.…”
Section: Introductionmentioning
confidence: 99%